George B. McClellan papers - McClellan, George B. (George Brinton), 1865-1940.
Correspondence, diary of military experiences in World War I, lectures, writings, subject files, printed matter, scrapbooks kept as a student at Princeton, printed matter, photographs, and other papers relating chiefly to McClellan's political career as a public official in New York City and as U.S. representative from New York. Includes correspondence, of McClellan's parents, George Brinton McClellan and Ellen Marcy McClellan. Other correspondents include Nicholas Murray Butler, Grover Cleveland, J.J. Jusserand, Robert Lansing, Robert Todd Lincoln, Henry Cabot Lodge, J. Pierpont Morgan, Alfred Emanuel Smith, William H. Taft, Henry Van Dyke, and Woodrow Wilson.
U.S. representative from New York, public official of New York City, and educator.
Collection material in English, with French and Italian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McClellan, Ellen Marcy, -- 1838-1907 -- Correspondence; McClellan, George Brinton, -- 1826-1885 -- Correspondence; Morgan, J. Pierpont -- 1837-1913 -- Correspondence; Smith, Alfred Emanuel, -- 1873-1944 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Van Dyke, Henry, -- 1852-1933 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Princeton University -- Students; World War, 1914-1918.; New York (State) -- Politics and government -- 1865-1950.; New York (N.Y.) -- Politics and government; United States -- Politics and government -- 1865-1933.; Educators; Public officials -- New York (State); Representatives, U.S. Congress -- New York (State)